Awareness On Foreign Body Aspiration Among Mothers Of Under-Five Children Of A Community - Maharjan, Jamuna Laxmi (Journal of Manmohan Memorial Institute of Health Sciences, 2023)
Background: Foreign Body Aspiration (FBA) is the fourth leading cause of accidental death for children under five years of age. FBA is a life-threatening emergency and needs urgent intervention. Mother is the primary caregiver for the child who can prevent, identify and get prompt treatment of FBA for their children. The objective of the study was to assess awareness on FBA among mothers of under five children. Method: A descriptive cross-sectional study was conducted among 84 mothers of under-five children based on inclusion criteria using non-probability convenience sampling technique. A self-developed structured questionnaire was used using face to face interview technique to collect the data. Data was collected from 16th Jan.2022-14th Feb.2022. Data analysis and interpretation was done using descriptive and inferential statistics. Findings: The findings showed that majority of the respondents 52.4% had poor level of awareness on FBA. The findings of the study showed low level of awareness on causes, signs and symptoms, preventive measures, management, complications. Majority of the respondents (91.7%) replied male child as risk gender & 89.3% respondents answered 1-5 years children having maximum chances of FBA. There is no significant association between level of awareness and Socio-demographic variables. Conclusion: More than half of the respondents had poor level of awareness on FBA. Therefore, study emphasizes on need to create more awareness about causes, signs and symptoms, prevention, management and complications among mothers of under-five children.